Dampak Sengketa Kepulauan Senkaku antara Jepang - Cina Terhadap Stabilitas Keamanan Jepang - Tjhang Zahra Anisa Pramaiseilla (Journal of International Relations, 2023)
The Senkaku Islands are rich in oil and gas resources, which has led Japan and Cina to claim each other that the Senkaku Islands belong to them. The impact of the dispute on Japan's security stability makes the senkaku islands and Japanese territories threatened and insecure because Cina conducts military operations by arming fishermen to become "maritime militias" and Cina has also increased their air activities, conducted training for their pilots and even created and enforcing air defense zones so that Japan's security stability becomes insecure and causes the Japanese state to be wary of attacks given by Cina because Cina sends military forces to Japan's territory which makes the Japanese region less secure while it has an impact on the economy and relations between Japan and the United States. Cina is going bad. The Japanese government's passive attitude that has been applied so far has turned into a proactive one by strengthening the military and surveillance system with advanced technology. To improve its national security, Japan increased their military budget and created military bases to deal with possible invasions from Cina in certain places around the Senkaku Islands.This study uses qualitative methods with descriptive explanatory data collection techniques. Techniques for data collection were carried out using literature studies obtained from journals, articles and books. The author will analyze the data with Process Tracing which will track a conflict process that can occur and explain the data according to the framework of each country's thinking because Japan and Cina mutually claim the Senkaku island belongs to each other and are a threat to the security of the Japanese region. The author uses the concept of National Security in analyzing the dispute between the senkaku islands of Japan and Cina as well as threats to the security stability of the Japanese region. Keywords: Dispute, Japan, Cina, Senkaku Island, UNCAFE, National Security.